ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP VOLUME PENYALURAN KREDIT PERBANKAN - Uswatun Khasanah; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
Bank as agent of service plays a role in channeling funds collected from the community who have excess funds to communities in need of funds. With this activity the bank should have the ability to manage the velocity of money in order to fulfill the demand of credit. This research is motivated because of not optimal distribution of bank loans. So, this was conducted to obtain evidence about the effect of internal and external factors, namely Deposit from Third Party, Loan to Deposit Ratio, Capital Adequacy Ratio, Non-Performing Loans, Return on assests, Operating Expenses to Operating Income, and Bank Indonesia Certificates to policy total of loans.This study used a sample of commercial banks listed on the Indonesia Stock Exchange (IDX) in the year 2010 to 2013 as many as 32 banking companies that have met predetermined criteria, so that when multiplied by years of research, it will get a sample of 96 banking data point to  use.  The  analysis  method  used  in  this  research  is  multiple  linear  regression  model,  the independent variables are DPK, CAR, LDR, NPLs, ROA, ROA, and SBI. The dependent variable is the credit.Based on the testing that has been done on this study gives results that DPK, CAR, LDR and NPL have a positive and significant effect to total of loans. While ROA and BOPO have negative and no significant effect to total of loans. Meanwhile, SBI have a negative and significant effect to total of loans.